An update on minimally invasive therapies for pancreatic necrosis. (December 2012) - Easler, Jeffrey J; Zureikat, Amer; Papachristou, Georgios I
Pancreatic necrosis is a local complication of severe acute pancreatitis associated with multiple organ dysfunction, infection and increased mortality. While surgery is the mainstay for invasive management, studies have demonstrated that delaying necrosectomy translates to improved patient outcomes. Minimally invasive therapies have been described both for early and late management of necrotic pancreatic collections and fall into three broad categories: endoscopic, radiology assisted percutaneous drainage and laparoscopic or retroperitoneal surgical techniques. Such interventions may serve as temporizing measures delaying necrosectomy, but more importantly, as best demonstrated in recent randomized controlled trials, can serve as alternative approaches resulting in improved patient outcomes. Access to these techniques is based on their availability at expert centers. Minimally invasive therapies have increased in popularity, with a general consensus among experts being that reduced complications and mortality rates are realized by approaches other than open necrosectomy. However, additional well-designed, randomized trials are needed.